(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Background: Medication non-adherence is a pervasive global challenge, particularly in the management of chronic diseases, leading to suboptimal health outcomes, increased morbidity and mortality, and substantial economic burden on healthcare systems. Pharmacists, as the most accessible healthcare professionals, are uniquely positioned to identify and address adherence barriers. Objective: To comprehensively review the types, methodologies, and effectiveness of pharmacist-led interventions aimed at improving adherence to chronic medications, and to analyze the key factors contributing to their success. Methods: A narrative review of current literature was conducted. Databases such as PubMed, Scopus, and Cochrane Library were searched for studies (randomized controlled trials, systematic reviews, meta-analyses) published between 2013 and 2023 using keywords: "pharmacist," "intervention," "medication adherence," "compliance," "chronic disease." Results: Evidence consistently demonstrates that multifaceted pharmacist interventions significantly improve medication adherence across various chronic conditions, including hypertension, diabetes, and hyperlipidemia. Effective strategies include patient education, medication therapy management (MTM), blister packing, reminder systems, and motivational interviewing. These interventions lead to statistically significant improvements in clinical outcomes (e.g., HbA1c, BP, LDL-C control) and generate positive economic returns by reducing hospitalizations and emergency department visits. Conclusion: Pharmacist-led interventions are a highly effective and cost-beneficial approach to tackling the problem of medication non-adherence. Integrating pharmacists as essential members of collaborative healthcare teams and compensating them for cognitive services is crucial for scaling these interventions and improving public health.